MODERN UKRAINIAN SOCIAL-DEMOCRACY IN SEARCHING FORMS OF INTERACTION WITH THE WORLD ORGANIZATION OF SOCIAL DEMOCRACY - Притуляк, С. І.; Притуляк, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the prospect of social democratic ideology is analysed in Ukraine. Ideological and political positions of modern Ukrainian social democratic political parties, that officially declared a policy of cooperation with the Socialist International, are investigational. It is proved that states of the former "socialist camp", the former Soviet republics, including Ukraine, are constantly in the spotlight of international social democracy.